An Overview of Cardiac Arrhythmia in COVID-19 Patients - Kamal, Anwar Abd-Al-Hameed; Saeed , Shrooq Majeed Mohameed (Jour Med Resh and Health Sci, 2023)
Early research indicates that the 2019 coronavirus disease (COVID-19) is linked to a significant prevalence of cardiac arrhythmias. Coronavirus 2 infections associated with severe acute respiratory syndrome may harm cardiac myocytes and increase the risk of cardiac arrhythmia. The current severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)or coronavirus disease 2019 (COVID-19) epidemic has rapidly spread to become a worldwide pandemic. Patients with and without a history of cardiovascular illness have had COVID-19-related cardiac problems, which are well-documented. Myocarditis, heart failure, and acute coronary syndrome brought on by coronary artery thrombosis or plaque ruptures brought on by SARS-CoV-2 are among the cardiac consequences. Arrhythmias are one of the main problems, as rising data indicates. As a potential arrhythmia mechanism, viral infection-induced myocardial inflammation results in electrophysiological and structural changes. This could also be how SARS-CoV-2 causes various arrhythmias. We talk about arrhythmia manifestations in COVID-19 in this review. , , ,